Relative age selection bias does not translate into a playing-time advantage: evidence from Italian Serie A football - Brustio, Paolo Riccardo; Ungureanu, Alexandru Nicolae; Beratto, Luca; Li Volsi, Damiano; Lupo, Corrado (Frontiers in Psychology, 2026)
IntroductionThe Relative Age Effects (RAEs) represent a bias in talent identification and selection processes, favouring athletes born earlier in the selection year. This study aimed to (i) quantify the prevalence and magnitude of the RAEs in Italian elite football (Serie A), considering age categories, playing positions, and team ranking, and (ii) examine whether RAEs are associated with selection- and participation-related outcomes (i.e., match appearances, total playing time, and consistency of match participation).MethodsData from 789 Serie A players were analysed.ResultsQ1 players were overrepresented compared with Q4 players (OR=1.9 [1.5–2.6]). RAEs were more pronounced in younger players (OR=2.1 [1.4–3.2]) and more evident among goalkeepers (OR=4.4 [1.8–10.6]) followed by forwards (OR=2.0 [1.0–3.8]), midfielders (OR=1.9 [1.1–3.1]) and defenders (OR=1.6 [1.0–2.4]). Moreover, RAEs were stronger in lower-tier teams (OR=2.5 [1.4–4.5]) than in top-tier teams (OR=1.5 [0.8–2.7]). No differences were observed between quartiles in selection- and participation-related outcomes.DiscussionRAEs persist in Serie A rosters but appear to operate primarily as a selection-level bias within talent development and squad selection, affecting which players reach and remain at the elite level, rather than influencing coaches’ decisions regarding match participation once players are part of the professional environment.